Mandarin Language in The Happy Sunday Program on Cakrawala Radio 98.3 FM - Siregar, Feby Yoana; Wenny, Wenny; Romy, Elly (Confucius Institute Universitas Sebelas Maret, 2023)
This research is motivated by Mandarin, which is not limited to economics, business, and education but also to the entertainment sector, especially radio broadcasts. The problem formulation in this research is how to use Mandarin in the Happy Sunday program on Radio Cakrawala, the obstacles in using Mandarin, and the solutions. The data collection techniques used in this research were observation, interviews and literature study. The research results show that the use of Mandarin in the Happy Sunday program dominates 75% of the total content of the program, and the remaining 25% is in Indonesian. This can be seen in its use in the opening of the event, the announcer's comments and the event's closing. Several obstacles were encountered, such as using varied language, language that attracted listeners, and the broadcaster's limited Mandarin vocabulary.